1250 Mbit/s OOK Wireless White-Light VLC Transmission Based on Phosphor Laser Diode - Chien-Hung Yeh; Chi-Wai Chow; Liang-Yu Wei (IEEE Photonics Journal)
In this work, for the first time, we demonstrate a 1250 Mbit/s on–off keying white-light visible light communication (VLC) transmission in a free space transmission length of 1 m by utilizing a yellow-phosphor laser diode (LD). Here, the blue optical filter, which is used to enhance the data rate by removing the yellow color component, is not required to. Besides, the wireless transmission lengths, illuminations, and modulation traffic rates of the proposed LD-based VLC system are analyzed and discussed.